Theoretical studies on the low-lying electronic states of N2O: From structural aspects to reaction dynamics - Li, Jing (2014)
This thesis is organized as follows: Part I concerns with the theoretical background, Part II refers to publications, Finally, the main achievements are summarized and further possible applications are outlined in Part III.